Optimizing Auditor Performance : Examining the Mediating Role of Communication in the Work Environment - Indrastuti, Sri; Mardianty, Desy; Hasan, Hazwari; Nugroho, Gilang (Atestasi : Jurnal Ilmiah Akuntansi, 2024)
This research has high significance in the context of operational efficiency and effectiveness of the Riau Province Inspectorate Office as well as improving employee performance. There is a lack of research regarding the role of communication, so researchers explore it further through a deeper understanding of the interaction between communication and the work environment and provide valuable insights for management to improve internal communication strategies, manage the work environment, and design policies that support the performance of auditor employees. This research approach is quantitative, with sampling using a cluster random sampling technique involving 121 auditor respondents. Data analysis was carried out using SEM with SMART PLS 4 processing. Research findings suggest that the work environment influences auditor performance and communication contributes as mediation, which strengthens the influence of the work environment on auditor performance. In conclusion, communication plays a role in mediating the influence of the work environment on the performance of auditors at the Riau Province Inspectorate Office. Thus, these findings can be used as a basis for developing more effective management strategies by prioritizing the role of communication in improving the quality of auditor performance.